Tertiary Education in Colombia - OECD; World Bank (Paris: OECD Publishing, 2017)
In Colombia, the beginning of a new century has brought with it a palpable feeling of optimism. Colombians will need new and better skills to apply to new challenges and prospects. The past underperformance of Colombia's education system is both a cause and an effect of a system unable to provide high quality education to all. An "education revolution" has begun and progress is being made. Basic and secondary enrolment, quality and learning outcomes are trending upward. The government's main policy goals at the tertiary level focus on the key challenges: expanding enrolment and improving equity, increasing quality and relevance, and making governance and finance more responsive. To achieve these goals, policy makers and stakeholders must find ways to reach consensus, work together and overcome inertia. Colombia has drifted away from focusing exclusively on the needs of students, the graduates they become, and the society in which they live and work. Restoring the focus on how tertiary education can serve these needs is a good organizing principle for reform. The government developed a proposed reform of Law 30 - the main statute governing tertiary education - and vigorous national debate accompanied its dissemination. Opposition to for-profit education dominated the headlines, but, in the review team's view, other aspects of the proposed reform were and are more important. The dramatic increase in tertiary enrolment witnessed during the last decade has also resulted in a more equitable distribution of access to tertiary education. The goal of enrolling 50% of the age cohort is appropriate and achievable, but it implies new challenges for access and student finance policies. The tertiary system covers the full range of the Colombian economy's needs for skilled manpower, if not necessarily to an equal extent. The government has clear and well-founded plans and aspirations for future tertiary growth and development. The Colombian government and people are well aware that they need not only more, but also better and fairer, tertiary provision - growth in coverage must be accompanied by quality, relevance and equitable access. The Colombian system of propaedeutic cycles is a good step towards allowing students to progress up through the tertiary levels. Colombian tertiary institutions have considerable autonomy, which is valuable in many ways though limiting in others.